SUPERIOR MADRASAH DEVELOPMENT STRATEGY IN MAN 2 MODEL MEDAN - Muhammad Rizki Syahputra (UIN Sumatera Utara Medan, 2021)
This study aims to determine the Development Strategy of Superior Madrasah in MAN 2 Medan Model and the Supporting and Inhibiting Factors of Excellent Madrasah Development Strategy at MAN 2 Medan Model. This study uses a qualitative research method that aims to understand a social phenomenon by prioritizing the process of deep interaction and communication between researchers and the phenomenon under study. The data obtained in this study are descriptive analysis, in which data collection is carried out by means of observations and interviews, and documentation studies. Then the data is presented in descriptive narrative form. The location of this research was carried out at MAN 2 Model Medan. The results showed that the superior madrasa development strategy carried out an effort to plan and manage madrasas that functioned to direct and develop madrasas in achieving their educational goals, because superior madrasas were intended as centers of excellence. The strategy for developing superior madrasah at MAN 2 Model Medan involves many related parties, starting from the guardians of students, teachers, madrasa heads and vice principals, as well as committees. A plan must have implementation, for the implementation of the strategy for developing the Madrasah Aliyah MAN 2 Medan Model is carefully calculated because implementation is one of the keys to the success of a superior madrasa development strategy so that the strategies implemented can run effectively so as to achieve success in program implementation For this reason, MAN 2 Model Medan has taken more actions to accelerate the implementation of the mutually agreed plan. Supporting factors in the superior madrasah development strategy are of course interrelated with the madrasa development strategy program, namely the partnership factor because partnerships have a very large effect on the development of madrasah.